2008
DOI: 10.1007/s00432-008-0424-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal metastasis of lung cancer with special emphasis on a long-term survivor after operation

Abstract: Physicians should be familiar with unique features of lung cancer with metastasis to the gastrointestinal tract so as to render early and optimal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 12 publications
2
105
3
1
Order By: Relevance
“…A recent report described by Kim et al [8] revealed that GI metastases were detected in 10 (0.19%) of 5239 lung cancer patients. In an autopsy study from Japan, the rate of GI tract metastasis, excluding the esophagus, was 1.8% and the colonic metastasis rate was only 0.5% [6] .…”
Section: Discussionmentioning
confidence: 95%
“…A recent report described by Kim et al [8] revealed that GI metastases were detected in 10 (0.19%) of 5239 lung cancer patients. In an autopsy study from Japan, the rate of GI tract metastasis, excluding the esophagus, was 1.8% and the colonic metastasis rate was only 0.5% [6] .…”
Section: Discussionmentioning
confidence: 95%
“…[4] The gastrointestinal tract is relatively rare site for metastasis from primary lung tumors, and of those cases the colon is only involved in 0.2%-0.5% of cases. [5,6] There exist very few case reports of symptomatic colonic involvement of primary lung lesions. A recent review identified only 14 such cases in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the small bowel, the most common metastatic site of lung cancer is the GI tract [30,31], and there have been a few reports of lung cancer metastases to the colon, appendix, or anus [32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%